Analisis Keterampilan Shooting dan Passing Pada Sekolah Sepak Bola - Syahruna, Duta Akbar; Nurhidayat, Nurhidayat (Jurnal Porkes, 2022)
In football games players must be able to master the basic techniques in football. This is because basic techniques are very helpful for the player to play the ball well and be able to carry out the strategy of the coach. Especially when shooting and passing. The purpose of this study was to find out how much shooting and passing ability in players of the Kebumen Regency Perseka Football School. The method in this study uses quantitative research methods with a descriptive approach. The data collection process was carried out by conducting shooting tests, flat passing, and stomach passing, with the number of subjects taken by 20 players. The sample was selected using a purposive sampling technique. Based on the results of this study, shooting and passing skills at the Perseka Football School, Kebumen Regency showed that shooting skills had a mean of 11.75 ± 2.83 in the medium category, flat passing had a mean of 42 ± 6.32 in the very good category, gastric passing had a mean of 42 ± 6.32. mean 149.5 ± 40.97 still in the less category. By knowing these results, it can be concluded that the shooting ability in the medium category, the flat passing ability in the very good category, the stomach passing ability in the less category.